How does the gut microbiome influence immune checkpoint blockade therapy? - Almonte, Andrew A; Rangarajan, Hareesha; Yip, Desmond; Fahrer, Aude M (Immunology and cell biology, 2021)
Immune checkpoint blockade (ICB) therapies are revolutionary cancer treatments; however, they only benefit about a third of patients. Therefore, extensive research is underway to find methods to improve their therapeutic efficacy. One avenue of study that has recently emerged is to consider the role the gut microbiome plays in therapeutic success. Several high-impact studies have repeatedly shown that the presence, composition and level of diversity of the gut flora directly impact cancer treatment outcome in both mice and patients. These studies have also highlighted the danger of using antibiotics shortly before or during cancer treatments. However, there are still several questions that need to be answered, including which bacteria promote the greatest benefit, the mechanisms by which they act and how we can use this information to influence treatment outcome. In this review, we explain how the gut microbiome was realized to be of such importance and propose hypotheses for why gut flora have such a critical impact on ICB therapeutic success. We also describe a hypothetical mechanism involving bacterial translocation out of the gut and into the tumor, whereby the bacteria act in an adjuvant capacity to facilitate an antitumor response. By highlighting key papers in the field, we hope to hasten research on the subject so as to find a means to improve the therapeutic efficacy of these ground-breaking cancer treatments.